Action of the insect growth regulator fluazuron, the active ingredient of the acaricide Acatak®, in Rhipicephalus sanguineus nymphs (Latreille, 1806) (Acari: Ixodidae) - Calligaris, Izabela Braggião; Oliveira, Patricia Rosa de; Roma, Gislaine Cristina; Bechara, Gervásio Henrique; Camargo-Mathias, Maria Izabel (Wiley, 2013)
The present study evaluated the efficacy of fluazuron (active ingredient of the acaricide Acatak®) and its effects on Rhipicephalus sanguineus nymphs fed on rabbits exposed to different doses of this insect growth regulator. Three different doses of fluazuron (20 mg/kg, 40 mg/kg, and 80 mg/kg) were applied on the back of hosts (via pour on), while distilled water was applied to the Control group. On the first day of treatment with fluazuron (24 h), hosts were artificially infested with R. sanguineus nymphs. Once fully engorged, nymphs were removed and placed in identified Petri dishes in Biochemical Oxygen Demand (BOD) incubator for 7 days. After this period, engorged nymphs were processed for ultramorphological analysis. The results revealed alterations in the ultramorphology of many chitinous structures (smaller hypostome and chelicerae, less sclerotized scutum, fewer sensilla, fewer pores, absence of grooves, marginal and cervical strips and festoons in the body, even the anal plaque was damaged) that play essential roles for the survivor of ticks and that can compromise the total or partial development of nymphs and emergence of adults after periodic molting. Our findings confirm the efficacy of fluazuron, a more specific and less aggressive chemical to the environment and human health, and that does not induce resistance, in nymphs of the tick R. sanguineus in artificially infested rabbits treated with this arthropod growth regulator (AGR), indicating that it could be used in the control of this stage of the biological cycle of the tick R. sanguineus. © 2013 Wiley Periodicals, Inc.
Keywords: Acaricide; Control; Cuticle; Integument; Ticks